2021
DOI: 10.21203/rs.3.rs-139366/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of Farmers on Pesticide Use and Their Impacts on the Environment and Human Health From Small Scale Vegetable Farming Along the Littoral of Lake Ziway, Ethiopia

Abstract: Background: The insecure utilization and misapplication of pesticides in Ethiopia are major fears to farmers' wellbeing and the ecosystem. This study aimed to assess the level of knowledge, attitude, and practices of the small-scale vegetable farmers towards the use of pesticides in Ethiopia along the littoral of Lake Ziway. Methods: It was a cross-sectional study involving a total of 210 farmers randomly selected during pesticide application from a purposively selected irrigation-using village located in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Although there are various methods to control insects, currently, chemical insecticides are principally used in the management of leaf miner. Several studies, however, showed that continuous use of the chemicals are implicated with destruction of natural enemies, buildup of insecticide residues on tomato fruits, and the environment, rapid development of insecticide resistance, and reduced profits from high insecticide costs [ 9 , 10 , 11 ]. This necessitates a shift from conventional pest control practices to integrated pest management (IPM), in order to reduce application of pesticides and produce healthy food [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are various methods to control insects, currently, chemical insecticides are principally used in the management of leaf miner. Several studies, however, showed that continuous use of the chemicals are implicated with destruction of natural enemies, buildup of insecticide residues on tomato fruits, and the environment, rapid development of insecticide resistance, and reduced profits from high insecticide costs [ 9 , 10 , 11 ]. This necessitates a shift from conventional pest control practices to integrated pest management (IPM), in order to reduce application of pesticides and produce healthy food [ 12 ].…”
Section: Introductionmentioning
confidence: 99%